2022
DOI: 10.1186/s40780-022-00252-z
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant palonosetron ameliorates cisplatin-induced nephrotoxicity, nausea, and vomiting: a retrospective cohort study and pharmacovigilance analysis

Abstract: Background Cisplatin (CDDP)-induced nephrotoxicity is the most important complication of CDDP treatment. 5-Hydroxytryptamine type 3 receptor antagonists (5-HT3RAs) are widely used to prevent chemotherapy-induced nausea and vomiting (CINV). However, in patients with the triple antiemetic (neurokinin-1 receptor antagonist, 5-HT3RA, and dexamethasone) therapy, the advantage of palonosetron in comparison with other 5-HT3RAs on CDDP-induced nephrotoxicity and CINV remains unclear. In the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Therefore, protecting the renal function during administration is needed. However, a study indicated that the first-generation 5-HT 3 R antagonists (ondansetron, granisetron, tropisetron) exacerbated cisplatin-induced renal injury, whereas the second-generation 5-HT 3 R antagonists (palonosetron) showed greater anti-cisplatin-induced nephrotoxicity than other 5-HT 3 R antagonists [114, 115]. A study reported that ondansetron is associated with an increasing risk of AKI [116].…”
Section: Protective Effects and The Latest Research Of Sedative And A...mentioning
confidence: 99%
“…Therefore, protecting the renal function during administration is needed. However, a study indicated that the first-generation 5-HT 3 R antagonists (ondansetron, granisetron, tropisetron) exacerbated cisplatin-induced renal injury, whereas the second-generation 5-HT 3 R antagonists (palonosetron) showed greater anti-cisplatin-induced nephrotoxicity than other 5-HT 3 R antagonists [114, 115]. A study reported that ondansetron is associated with an increasing risk of AKI [116].…”
Section: Protective Effects and The Latest Research Of Sedative And A...mentioning
confidence: 99%